2018
DOI: 10.1007/s10811-018-1414-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of depth and initial fragment weights of Gracilaria gracilis on the growth, agar yield, quality, and biochemical composition

Abstract: phycoerythrin is considered to be a predominant pigment in red algae. This pigment is at present used in food industry as colorant. Nevertheless, because of the spectral properties, it is used mainly in clinical and immunological analysis (Mensi et al.2012), in fluorescence microscopy and flux cytometry (Glazer and Stryer 1984;Kronick 1986). It is also reported that R-phycoerythrin and phycocyanin act as a part of protective mechanism in seaweeds in general (Sinha et al.1995) and in Gracilaria caudata particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
11
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
(54 reference statements)
4
11
1
1
Order By: Relevance
“…The higher agar yields obtained in the BB, could be due to the high salinity level, light quantity and a lower nitrate concentrations than that recorded in the BL 39 . The culture depth of G.gracilis in the BL and the BB didn't affect the agar yields in contrary to previous findings in the BL by 9 , which indicated a higher agar yields at a depth of 2 m compared to those obtained at 0.5 m. Unlike the previous work, this study was performed in the eastern part of the lagoon, characterized by a higher www.nature.com/scientificreports www.nature.com/scientificreports/ turbidity (Secchi depth <0.5 m). Consequently, the amount of light is insufficient (<70 µmol m 2 s −1 ) to interact with other factors and allowing the alga to produce higher agar yields 39,62 .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The higher agar yields obtained in the BB, could be due to the high salinity level, light quantity and a lower nitrate concentrations than that recorded in the BL 39 . The culture depth of G.gracilis in the BL and the BB didn't affect the agar yields in contrary to previous findings in the BL by 9 , which indicated a higher agar yields at a depth of 2 m compared to those obtained at 0.5 m. Unlike the previous work, this study was performed in the eastern part of the lagoon, characterized by a higher www.nature.com/scientificreports www.nature.com/scientificreports/ turbidity (Secchi depth <0.5 m). Consequently, the amount of light is insufficient (<70 µmol m 2 s −1 ) to interact with other factors and allowing the alga to produce higher agar yields 39,62 .…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, the agar obtained in the BL is of lower quality due to the lower percentage of 3,6-AG and higher sulphate degree (23.30 ± 5.40% of 3,6-AG and 8.80 ± 0.86% of sulphate). Similar results were obtained in the BL 9 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Previous research showed that G. gracilis biochemical composition is dependent on the depth it grows. For instance, the total lipid content was higher in the seaweed cultured at a depth of 2.5 m than the seaweed cultivated at 0.5 m [ 63 ]. Nevertheless, researchers studied G. gracilis FA profile variation during the harvesting season and found that the total content and the lipid (and fatty acid in particular) composition of this seaweed collected at the Lesina lagoon (Italy) is higher and more diverse in the spring and lower and less diverse in the autumn [ 60 ].…”
Section: Discussionmentioning
confidence: 99%